Pengembangan Aplikasi Marketplace Untuk Jasa Konfeksi - Muhammad Iqbal Kurniawan; Bayu Priyambadha; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Custom clothing manufacturing is one of the bustling businesses with the growth of SMEs production of apparel reaching 7.05 percent in 2018 based on data from the Central Statistics Agency. Through current technological developments, the use of technology for economics can provide benefits for SMEs such as custom clothing manufacturing. However, the application of e-marketplace that already exists in Indonesia do not provide adequate functions for the process of ordering custom clothing. Therefore, ordering custom clothing service cannot be made through an existing e-marketplace application. The problem that occurs in the conventional process is that customers are having trouble finding appropriate prices from various custom clothing merchants, customers have trouble monitoring the progress of the order and the processing period is not clear. Based on these problems, developing e-marketplace applications for custom clothing manufacturing is expected to solve these problems. The first process of the research is requirements analysis and obtained 28 functionals and 2 non-functionals functions, namely compatibility and performance. Then the system design process and system implementation process are carried out that refers to the acquisition of the requirement analysis process. The application implementation uses PHP based Laravel framework. Unit and integration level test results, as well as validation testing of the application, are 100 percent valid. The compatibility test results show that the application has no compatibility issues and can run on multiple platforms. The performance test results show that the application has an average performance that is the application can be accessed within a period of 1 to 2.5 seconds.